The effects of four weeks of creatine supplementation and high-intensity interval training on cardiorespiratory fitness: a randomized controlled trial - Graef, Jennifer L (BioMed Central, 2009)
BACKGROUND: High-intensity interval training has been shown to be a time-efficient way to induce physiological adaptations similar to those of traditional endurance training. Creatine supplementation may enhance high-intensity interval training, leading to even greater physiological adaptations. The purpose of this study was to determine the effects of high-intensity interval training (HIIT) and creatine supplementation on cardiorespiratory fitness and endurance performance (maximal oxygen consumption (VO(2PEAK)), time-to-exhaustion (VO(2PEAK)TTE), ventilatory threshold (VT), and total work done (TWD)) in college-aged men. METHODS: Forty-three recreationally active men completed a graded exercise test to determine VO(2PEAK), VO(2PEAK)TTE, and VT. In addition, participants completed a time to exhaustion (TTE) ride at 110% of the maximum workload reached during the graded exercise test to determine TWD (TTE (sec) × W = J). Following testing, participants were randomly assigned to one of three groups: creatine (creatine citrate) (Cr; n = 16), placebo (PL; n = 17), or control (n = 10) groups. The Cr and PL groups completed four weeks of HIIT prior to post-testing. RESULTS: Significant improvements in VO(2PEAK )and VO(2PEAK)TTE occurred in both training groups. Only the Cr group significantly improved VT (16% vs. 10% improvement in PL). No changes occurred in TWD in any group. CONCLUSION: In conclusion, HIIT is an effective and time-efficient way to improve maximal endurance performance. The addition of Cr improved VT, but did not increase TWD. Therefore, 10 g of Cr per day for five days per week for four weeks does not seem to further augment maximal oxygen consumption, greater than HIIT alone; however, Cr supplementation may improve submaximal exercise performance.